Intergenerational Educational Mobility and Preferences for Redistribution in Europe: Intergenerational Mobility and Redistributive Preferences - Torul, Orhan; Öztunalı, Oğuz (Journal of Income Distribution®, 2024)
We study how preferences for redistribution vary at the individual level in Europe. Using survey data from a large subset of European countries, we show that controlling for socio-economic and demographic characteristics, personal intergenerational educational movements play a decisive role in redistributive preferences: individuals with low educational attainment and born to low-educated parents favor redistributing incomes more. Matching subjects with their experienced country-cohort-gender-specific intergenerational educational mobility estimates, we further show that individuals whose clusters faced better upward mobility prospects when growing up are more in favor of equalizing incomes. We offer a parsimonious economic model that accords well with these novel findings.